Media Health Literacy - Hadi Tehrani (Mashhad University of Medical Sciences, 2016)
Background and objective: Many people agree that media are the biggest trainer in modern societies. People in the modern societies spend most of their time to seeing the Medias after sleeping. Therefore the content of the media should be the consideration in various fields, especially in public health. Media literacy attributed to the strengthening of media experiences. Some researchers have been defined media literacy as follows: The ability to access, analyze, evaluate and communicate with media messages in various forms. In other words, media literacy is perspective that we actively use it for media exposure to interpret the meaning of the messages that we encountered. Thus, this study aims to explain the concept of media literacy Paper Type: letter to editor.